RESPONSE TO INTRADERMAL ROUTE OF HEPATITIS B VACCINATION IN CHILDREN ON MAINTENANCE HEMODIALYSIS: A SINGLE CENTER EXPERIENCE - Khan, Kalimullah; Zubair, Aasia; Madiha Aziz; Agha, Sanaullah; Kumar, Pawan; Hashmi, Seema (Infectious Diseases Journal of Pakistan, 2023)
Background: To determine the response of intradermal route of hepatitis B vaccine (HBV) in pediatric dialysis patients. Material and Methods: Prospective, observational study carried out in the Hemodialysis Unit, Sindh Institute of Urology and Transplantation (SIUT), Karachi, from October 2021 to September 2022.Patients younger than 18 years, Hepatitis B surface antigen negative irrespective of primary vaccination status, were tested for anti-Hepatitis B antibody titers. Those with levels less than 10IU/L were recruited for intradermal vaccination at 0,1 and 6 months and titers rechecked in the 2nd and 7th month of study. Results: Of the 168 children screened, 81 (48%) patients were eligible for vaccination, however, 52 agreed to participate. Males were 27 (52%). Mean age was 12.18± 2.61 years. End-stage kidney disease due to unknown etiology was the most common cause in 27 (52%) patients with mean dialysis duration being 1.43±1 years. Most, 48 (92%) patients were hypertensive and majority, 47 (90%) patients tested negative for hepatitis C. Final analysis was done on 38 patients. Thirty-four (89.4%) patients responded; 25 (65.8%) being good and excellent responders. Mean antibody titers before intradermal vaccination of 2.87±3 IU/L improved to 383±397 IU/L. Ages 11-15 years showed a statistically significant association with the development of anti-Hepatitis B antibody titers (p value: 0.02) while gender, dialysis duration, pre-vaccination HBs titers, hepatitis C status, hypertension and cause of end-stage kidney disease did not have any effect. Conclusion: ID route of HBV is efficacious in producing seroprotective anti-HBs titers in pediatric ESKD patients. Children 11-15 years had more robust response. Keywords: Children, Hemodialysis, Hepatitis B, Intradermal, Vaccination